Influence of repetitive diving in freshwater on pressure equalization and Eustachian tube function in recreational scuba divers - Jansen, Stefanie (Diving Hyperb Med, 2017)
INTRODUCTION: We investigated the effect of repetitive pressure exposure during freshwater dives on Eustachian tube function and the middle ear, assessed by the Eustachian tube function test (ETFT). METHODS: This prospective observational cohort study included 23 divers over three consecutive days of diving in freshwater lakes in Nordhausen, Germany. Participants underwent otoscopy and ETFT before the first dive, between each dive and after the last dive. ETFT included regular tympanometry (R-tymp), tympanometry after Valsalva (V-tymp) and after swallowing (S-tymp). The peak pressure difference between the R-tymp and the V-tymp (R-V(dP)) defined effectiveness of pressure equalization after Valsalva manoeuvres. We evaluated the change in compliance and peak pressure and correlated the results to the otoscopic findings and diving experience. RESULTS: Twenty-three divers performed 144 dives. Middle ear barotrauma was assessed using the Edmonds modification of the TEED scoring system. In the ETFT, the R-tymp peak pressure displayed a negative shift from day one to three (P = 0.001) and differed significantly between the experience groups (P = 0.01). R-V(dP) did not change significantly on any of the three days of diving (all P > 0.05). Participants without MEBt showed significantly lower R-tymp values than did those with barotrauma (P = 0.019). CONCLUSION: Repetitive pressure exposure during three consecutive days of freshwater diving led to a negative shift of the peak pressure in the middle ear. Less experienced divers showed significantly higher middle ear peak pressure and higher pressure differences after equalization manoeuvres. Higher middle ear peak pressure was also associated with a higher prevalence of barotrauma.